Exploring Academic Burnout: The Interplay of Time Pressure, Poor Sleep Habits, and Jam Koma Among Undergraduate Students in East Kalimantan - Rohana Nur Aini; Muhammad Ramadhani Kesuma; Ellen D. Oktanti Irianto; Margareth Henrika; Lusiana Desy Ariswati (SOSMANIORA: Jurnal Ilmu Sosial dan Humaniora, 2025)
This study investigates the interplay of time pressure, poor sleep habits, and jam koma as key predictors of academic burnout among university students in East Kalimantan. Utilizing a quantitative cross-sectional design, the research investigates how time pressure and poor sleep habits contribute to burnout, with cognitive fatigue locally termed “jam koma”, acting as a mediator. Data were collected from undergraduate students using instruments, including scales for time pressure, sleep quality, jam koma, and burnout, and analyzed through Structural Equation Modeling-Partial Least Squares. The findings reveal that time pressure and inadequate sleep significantly drive burnout, both directly and indirectly through jam koma, highlighting the mediating role of mental exhaustion in amplifying academic stress. These results extend the JDR model by incorporating sleep as a critical physiological resource, offering a nuanced understanding of burnout dynamics in collectivist academic settings. This study concludes the urgent need for culturally tailored interventions, such as time management training, sleep hygiene programs, and counseling services sensitive to collectivist values, to mitigate burnout and enhance student well-being. By providing localized insights into burnout mechanisms, this research informs evidence-based strategies for fostering resilient academic environments in East Kalimantan and similar collectivist contexts, contributing to global efforts to support student mental health.